2000
DOI: 10.1046/j.1365-2036.2000.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer prevention in ulcerative colitis: a case‐control study

Abstract: CRC risk among UC patients can be reduced by regular therapy with 5-ASA medication. Colonoscopic surveillance may be best targeted on those unable to take 5-ASAs (e.g. due to allergy) and those with a positive family history of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
330
3
33

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(379 citation statements)
references
References 38 publications
13
330
3
33
Order By: Relevance
“…[15][16][17][18][19][20] of the present study confirm and expand on these observations and suggest a potential mechanism by which 5-ASA could interfere with CRC cell growth. We would like, however, to point out that our results also suggest the possibility that 5-ASA may affect additional pathways other than EGFR that sustain CRC cell growth.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…[15][16][17][18][19][20] of the present study confirm and expand on these observations and suggest a potential mechanism by which 5-ASA could interfere with CRC cell growth. We would like, however, to point out that our results also suggest the possibility that 5-ASA may affect additional pathways other than EGFR that sustain CRC cell growth.…”
Section: Discussionsupporting
confidence: 83%
“…In recent years, evidence has also been provided to suggest that long-term consumption of 5-ASA reduces the rates of CRC developing in patients with ulcerative colitis. 15,16 Moreover, studies both in vitro and animal models of carcinogenesis have shown that 5-ASA negatively regulates the growth of CRC cells, [17][18][19][20] further supporting the antineoplastic properties of this drug. The molecular mechanism by which 5-ASA exerts the antiproliferative effect on CRC cells remains however unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Anti-inflammatory drugs that are known to inhibit IKK-dependent NF-B activity reduced the cumulative incidence of colitis-associated cancer in patients with ulcerative colitis, suggesting a role for NF-B in colonic tumor onset and/or progression. 4 In contrast, inhibition of NF-B in vivo promoted squamous cell tumors, [5][6][7] indicating the possibility of cell-type-specific roles for NF-B in tumorigenesis. Inactivation of I⌲K␤ in intestinal epithelial cells reduced colonic tumor formation in response to chemical procarcinogens, 8 implying that I⌲K␤ plays a key role in promoting enterocyte tumorigenesis.…”
mentioning
confidence: 99%
“…However, since folate deficiency has been associated with dysplasia, the anti-inflammatory effect of sulfasalazine, which is a competitive inhibitor of folate absorption, appears to be out-weighted by the effect of folate deficiency (9,13). Thus, it might be preferable for patients on long-term 5-ASA maintenance treatment to use nonsulfasalazine compounds.…”
Section: The Variable Risk Of Colorectal Cancer In Patients With Inflmentioning
confidence: 99%
“…It is therefore too early to conclude that the risk of colorectal cancer is lower in Greece than in other areas of the world. However, it will be of great interest to follow this cohort of patients for another [10][11][12][13][14][15] years to document whether the clinical impressions of mild IBD phenotypes and low incidence of extra-intestinal manifestations are truly reflected by a low incidence of dysplasia and colorectal cancer.…”
Section: The Variable Risk Of Colorectal Cancer In Patients With Inflmentioning
confidence: 99%